Driver's car following headway on single carriageway roads - Che Puan, Othman (Faculty of Civil Engineering, UTM, 2004)
One of many aspects that are considered to influence road crashes and road traffic handling capacity is the drivers' car following behaviour. This study examines the distance separation between impeded vehicles on single carriageway roads. Data defining headway and speed for more than 8000 vehicles were collected using video cameras to record traffic movement at four sites in Malaysia. The distance headways and associated vehicle speeds were separated into vehicle following category by vehicle type and then into speed classes for vehicle following vehicle: car following car, car following heavy goods vehicle (HGV), HGV following HGV and HGV following car categories. In most cases the lognormal distribution was found to be an appropriate representation of the variation in distance headways for vehicles within a particular speed class. Linear regression models were developed to represent the relationships between distance headway and speed and the predicted variation in population mean distance headway with vehicle speed. In general, Malaysian drivers tend to follow another vehicle closely and platoons appeared to develop rapidly.